New insights into the use and circulation of reindeer antler in northern Iberia during the Magdalenian (ca. 21-13 cal ka BP). (February 2023) - Lefebvre, A.; Pétillon, J.-M.; Cueto, M.; Álvarez-Fernández, E.; Arias, P.; Ontañón, R.; Berganza, E.; Marín-Arroyo, A.B.
Abstract: Interactions between prehistoric foragers and reindeer at the end of the Pleistocene are still poorly documented in northern Iberia, particularly the reasons and means by which their antlers were collected, processed and circulated. Here we review the main osseous industries dated to between 21 and 13 cal ka BP, focusing on the use and circulation of reindeer antler as a raw material for the production of weapons and tools by Magdalenian foragers. Thirty-six reindeer antler artefacts were identified from 11 Iberian sites that are located at either end of the Pyrenees: the Cantabrian region to the west, and to a lesser extent, in Catalonia to the east. Despite biases in the identification of production objectives (end-products), a detailed techno-typological, chronological and geographical analysis of these assemblages reveals both the existence of a consistent reindeer antler industry in northern Iberia and long-distance connections between the Cantabrian region and the Pyrenees. The integration of contemporary macrofaunal data makes it possible to explore the extension of the reindeer's ecological niche in northern Iberia, as well as strategies for the acquisition and circulation of reindeer antler in the peninsula. Assuming that some reindeer assemblages result from the import of raw materials to supply manufacturing activities, we propose a scenario where the acquisition of reindeer antlers may have been organised at a local scale in the Basque region, and potentially in the neighbouring territories of Navarre, Cantabria and Asturias. On the other hand, in Catalonia, the combination of both faunal and technological data supports the hypothesis that reindeer antlers were imported (along with pelts) over longer distances, probably from the northern Pyrenees. Highlights: Magdalenian foragers from northern Iberia regularly used reindeer antler for the manufacture of weapons and tools. First extensive database of Magdalenian antler technology in northern Spain. Common cultural traditions and long-distance connections within the Pyrenean-Cantabrian region. First map on the extension of the ecological niche of the reindeer in northern Iberia at the end of the Pleistocene. Introduction of reindeer antlers (along with pelts) from the northern Pyrenees into Catalonia.